Design and Development of a Smart Café System Utilizing IoT for Real-Time Remote Monitoring and Updates - Ningsih, Yuli Kurnia; Fuanisa Bonita (Emitor: Jurnal Teknik Elektro, 2024)
Currently, cafés are a popular place for community activity. In addition to enjoying drinks and food, the café is also a place that is used as a place for discussions, for learning/study and a meeting point for various groups, including students. A good café is one with comfortable and safe conditions. One way to ensure the comfort of café is to monitor and control the body temperature, air quality,room temperature and humidity, the number of visitors, cleanliness and the temperature in the kitchen. This research, an IoT based monitoring and control tools was developed. The goal of this tool is to monitor and control café conditions automatically real time and touchless. The sensors used collect data and read the conditions of parameters to be evaluated. Among the evaluations performed by this tool are the number of visitors (dine-in or take-away), control of temperature & humidity in the café, attendance tag cards for employees and cafe security, compliance with health protocols before entering the cafe, and measurement of a person’s body temperature using infrared. In addition, if there is an anomaly in the café (temperature exceedance), the manager receives a notification in real time of what is going on in the café. Cooling fans and humidifiers are activated when the air quality is abnormal, that is, when the temperature is more than 33°C and the humidity is not 45% - 65% Relative Humidity. When the temperature in the kitchen is more than 38°C, the alarm is activated